(untitled) (Brazilian Journal of Radiation Sciences, 2024)
For most purposes, the quality of a beam can be specified in terms of the half-value layer (HVL), which is the thickness of material required to reduce the air kerma to half, at one meter from the source, from a unidirectional beam of infinitesimal width. Just like many other radiological quantities of interest, the HVL can be estimated via simulations employing the Monte Carlo Method (MCM). Among the variety of MCM based codes available, the Particles and Heavy Ions Transport Code System (PHITS) was the one adopted in this study. Primarily, simulations were conducted to determine the X-ray spectra resulting from the interaction of electron beams with different energies with a tungsten anode. Each of these spectra was then defined as a probability distribution for the photon source energies in a second round of simulations, where it was possible to estimate the X-ray beam qualities as specified by the reference literature. At this stage, it was possible to estimate the mean energy of the beam and the conversion coefficient for air kerma per unit fluence for each of the qualities. The results obtained in this phase were used to define the sources for other groups of simulations, where the air kerma was quantified for each source configuration, for different thicknesses of an aluminum metallic attenuator, which was also done with spectra for the same X-ray beam qualities obtained from a reference catalog. Curve fitting on the scatter of kerma points as a function of attenuation allowed the estimation of the HVL. The results obtained are consistent with the values described in the literature and demonstrate the efficiency of the developed methodology, as well as the use of the code in the evaluated energy range for X-rays.